Changing the subject of an equation involves solving for another variable in the equation
The equation of t is ![t=\frac{\sqrt{y_i-y_o}}{N}](https://tex.z-dn.net/?f=t%3D%5Cfrac%7B%5Csqrt%7By_i-y_o%7D%7D%7BN%7D)
<h3>How to change the subject of the equation</h3>
The equation is given as:
![N=\sqrt[2]{\frac{y_i-y_o}{t^2}}](https://tex.z-dn.net/?f=N%3D%5Csqrt%5B2%5D%7B%5Cfrac%7By_i-y_o%7D%7Bt%5E2%7D%7D)
Rewrite the equation as:
![N=\sqrt{\frac{y_i-y_o}{t^2}}](https://tex.z-dn.net/?f=N%3D%5Csqrt%7B%5Cfrac%7By_i-y_o%7D%7Bt%5E2%7D%7D)
Evaluate the square root of t^2
![N=\frac{\sqrt{y_i-y_o}}{t}](https://tex.z-dn.net/?f=N%3D%5Cfrac%7B%5Csqrt%7By_i-y_o%7D%7D%7Bt%7D)
Multiply both sides by t
![Nt=\sqrt{y_i-y_o}](https://tex.z-dn.net/?f=Nt%3D%5Csqrt%7By_i-y_o%7D)
Make t the subject, in the above equation
![t=\frac{\sqrt{y_i-y_o}}{N}](https://tex.z-dn.net/?f=t%3D%5Cfrac%7B%5Csqrt%7By_i-y_o%7D%7D%7BN%7D)
Hence, the equation of t is ![t=\frac{\sqrt{y_i-y_o}}{N}](https://tex.z-dn.net/?f=t%3D%5Cfrac%7B%5Csqrt%7By_i-y_o%7D%7D%7BN%7D)
Read more about subject of formula at:
brainly.com/question/657646
Answer:
b/(b+a)
Step-by-step explanation:
(1/a)-(1/b) :[ (b²-a²)/ab²]
first solve :
common denominator ab
(1/a)-(1/b) = (b-a)/ab
[b-a/ab] : [(b²-a²)/ab²]
when divide fraction ( division sign turn to (×) and flip the second fraction(reciprocal):
[b-a/ab] × [ab²/ (b²-a²)]
then simplify : ab²/ab = b
(b-a)×(b/b²-a²)
factorize : b²-a² = (b-a)(b+a)
(b-a)×(b/(b-a)(b+a)) simplify : (b-a)/b-a = 1
[(b-a)(b)]/[(b-a)(b+a)
b/b+a
Well to divide 2 fraction you first have to find a least common number between the 2 bottom numbers in the fractions, we know automaticall that 15 fits in both the 3 and the 5. now u have to find out what to multiply by each number to get 15, for example what number do you multiply by 3 to get 15?? well it will be 5, so go ahead and multiply it by the fraction (note that what you do in the bottom you have to do in the top) this will give you 10/15, because I multiplied the top and bottom number by 5... lets try the other one what number do you multiply by 5 to get 15?? well it will be 3 so go ahead and multiply that to get 12/15.. now add the top numbers (note that the bottoms always stay the same, you never add or subtract them) when you do you will get 22/15, now you have to see if you can simplify it any further in this case you can't so your final answer is 22/15
Hope this helps
Answer:
The standard deviation of the sampling distribution of x overbarx, denoted sigma Subscript x overbarσx, is called the standard error of the mean . The standard deviation of the sampling distribution of x overbarx, denoted sigma Subscript x overbarσx, is called the standard distribution of the sample.
Step-by-step explanation:
The standard error (SE) of a statistic is the standard deviation of its sampling distribution or an estimate of that standard deviation. It is called the standard error of the mean (SEM) if the parameter or the statistic is the mean.
Below is the solution, I hope it helps.
<span>i) tan(70) - tan(50) = tan(60 + 10) - tan(60 - 10)
= {tan(60) + tan(10)}/{1 - tan(60)*tan(10)} - {tan(60) - tan(10)}/{1 + tan(10)*tan(60)}
ii) Taking LCM & simplifying with applying tan(60) = √3, the above simplifies to:
= 8*tan(10)/{1 - 3*tan²(10)}
iii) So tan(70) - tan(50) + tan(10) = 8*tan(10)/{1 - 3*tan²(10)} + tan(10)
= [8*tan(10) + tan(10) - 3*tan³(10)]/{1 - 3*tan²(10)}
= [9*tan(10) - 3*tan³(10)]/{1 - 3*tan²(10)}
= 3 [3*tan(10) - tan³(10)]/{1 - 3*tan²(10)}
= 3*tan(30) = 3*(1/√3) = √3 [Proved]
[Since tan(3A) = {3*tan(A) - tan³(A)}/{1 - 3*tan²(A)},
{3*tan(10) - tan³(10)}/{1 - 3*tan²(10)} = tan(3*10) = tan(30)]</span>